Integrated Design Optimization Process for Building Projects - Aslay, Semi Emrah; Dede, Tayfun; Kaveh, Ali (Periodica Polytechnica Civil Engineering, 2024)
In this study, a cost-design optimization is conducted for a reinforced concrete structure with irregular voids and inclined axes, which is a real-world application. Data transfers are performed on a 3D model to achieve the optimization. Data exchange is managed automatically by the created software program. As an application example, a hospital building with 10 beds is considered. Optimum design and minimum cost values are obtained for optimization processes using the Rao algorithms. The construction cost values are compared both among algorithms and with actual cost values, indicating a successful optimization process. The software program developed in this study accelerates the processes in optimization operations, thereby contributing to the realization of automatic data transfers.